Construction of ethics in clinical research - Clinical trials registration - Caramori, Carlos Antonio [UNESP] (FapUNIFESP (SciELO), 2007)
Scientific development that has been achieved through decades finds in clinical research a great possibility of translating findings to human health application. Evidence given by clinical trials allows everyone to have access to the best health services. However, the millionaire world of pharmaceutical industries has stained clinical research with doubt and improbability. Study results (fruits of controlled clinical trials) and scientific publications (selective, manipulated and with wrong conclusions) led to an inappropriate clinical practice, favoring the involved economic aspect. In 2005, the International Committee of Medical Journal Editors (ICMJE), supported by the World Association of Medical Editors, started demanding as a requisite for publication that all clinical trials be registered at the database ClinicalTrials.gov. In 2006, the World Health Organization (WHO) created the International Clinical Trial Registry Platform (ICTRP), which gathers several registry centers from all over the world, and required that all researchers and pharmaceutical industries register clinical trials. Such obligatory registration has progressed and will extend to all scientific journals indexed in all worldwide databases. Registration of clinical trials means another step of clinical research towards transparency, ethics and impartiality, resulting in real evidence to the forthcoming changes in clinical practice as well as in the health situation.
Keywords: Biomedical research; Clinical trials; Drug information services; Ethics; World health organization